BIOLOGY OF EPILACHNA SEPTIMA DIEKE (COCCINELLIDAE : COLEOPTERA) INFESTING MOMORDICA CHARANTIA WITH A NOTE ON ITS FEEDING DAMAGE - MAHALYA, J. LILY; JESUDASAN, R. W. ALEXANDER (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1996)
A study on the biology of Epilachna septima Dieke, was conducted from April to August, 1995, in the Department of Zoology, Madras Christian College (MCC), Madras. The descriptions, measurements and the period occupied by the different life stages of E. septima including the pre-oviposition, oviposition and post-oviposition period have been presented. An account on the feeding damage by the developing stages of the insect has been included.